Medium-scale traveling ionospheric disturbances created by primary gravity waves generated by a winter storm - Kogure Masaru; Chou Min-Yang; Yue Jia; Otsuka Yuichi; Liu Huixin; Sassi Fabrizio; Pedatella Nicholas; Randall Cora E.; Harvey V. Lynn (Journal of Space Weather and Space Climate)
This study explores the meteorological source and vertical propagation of gravity waves (GWs) that drive daytime traveling ionospheric disturbances (TIDs), using the specified dynamics version of the SD-WACCM-X (Whole Atmosphere Community Climate Model with thermosphere-ionosphere eXtension) and the SAMI3 (Sami3 is Also a Model of the Ionosphere) simulations driven by SD-WACCM-X neutral wind and composition. A cold weather front moved over the northern-central USA (90–100°W, 35–45°N) during the daytime of 20 October 2020, with strong upward airflow. GWs with ~500–700 km horizontal wavelengths propagated southward and northward in the thermosphere over the north-central USA. Also, the perturbations were coherent from the surface to the thermosphere; therefore, the GWs were likely generated by vertical acceleration associated with the cold front over Minnesota and South Dakota. The convectively generated GWs had almost infinite vertical wavelength below ~100 km due to being evanescent. This implies that the GWs tunneled through their evanescent region in the middle atmosphere (where a squared vertical wavenumber is equal to or smaller than 0) and became freely propagating in the thermosphere and ionosphere. Medium-scale TIDs (MSTIDs) also propagated southward with the GWs, suggesting that the convectively generated GWs created MSTIDs.